PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK GETARAN DAN GELOMBANG DI KELAS VIII SMP NEGERI 1 LIMA PULUH T.P 2013/2014 - Ida Wahyuni; Haris Samosir (INPAFI (Inovasi Pembelajaran Fisika), 2015)
This study aimed to know the effect of model inqury for the learning outcomes of students in the subject matter vibrations and waves in the eighth grade 2nd semester of SMP Negeri 1 Lima Puluh T.P. 2013/2014. The study population was all student of class VIII SMP Negeri 1 Lima Puluh consists of seven classes and the sample consists of two classes, specifically control class and experimental class taken by cluster random sampling. The author  had applied model inqury in the experimental class and convensional model in the control class. The study instrument used was a essay test. Postest results of experimental class is 66.80 and the control class is 45.43. Students activity at the time of implementation of model inqury has increased from 50.29% (enough active) at 1st meeting, 69.61% (active) at 2nd meeting and became 90.22% (very active) at 3rd meeting. The result indicates the learning outcomes of students using inqury model is higher than using convensional model. Keywords: Activities, Learning Outcomes, Inqury.